Characterisation of two novel genes encoding Δ9 fatty acid desaturases (CeSADs) for oleic acid accumulation in the oil-rich tuber of Cyperus esculentus. (June 2022) - Li, Teng; Sun, Yan; Chen, Ying; Gao, Yu; Gao, Huiling; Liu, Baoling; Xue, Jinai; Li, Runzhi; Jia, Xiaoyun
Abstract: Cyperus esculentus is considered one of the most promising oil crops due to its oil-rich tuber, wide adaptability and large biomass production. Preferable triacylglycerol (TAG) composition, especially high oleic acid content, makes tuber oil suitable for human consumption and biodiesel production. However, the mechanism underlying oleic acid enrichment in the tuber remains unknown. Plastidial stearoyl-ACP desaturase (SAD) catalyses the formation of monounsaturated fatty acids (MUFAs), which may function crucially for high accumulation of oleic acid in C. esculentus tubers. In this study, two full-length cDNAs encoding SAD were isolated from the developing tubers of C. esculentus, namely, CeSAD1 and CeSAD2, with ORFs of 1194 bp and 1161 bp, respectively. Quantitative RT-PCR analysis showed that CeSAD genes were highly expressed in tubers. The expression pattern during tuber formation was also significantly correlated with fatty acid and oil accumulation dynamics. Overexpression of each CeSAD gene could restore the normal growth of the defective yeast BY4389, indicating that both CeSADs had fatty acid desaturase activity to catalyse MUFA biosynthesis. A tobacco genetic transformation assay demonstrated that both CeSAD enzymes had high enzyme activity. Exogenous addition of exogenous fatty acids to feed yeast revealed that CeSAD1 has a more substantial substrate preference ratio for C18:0 than CeSAD2 did. Moreover, the overexpression of CeSAD1 significantly increased host tolerance against low-temperature stress. Our data add new insights into the deep elucidation of oleic acid-enriched oils in Cyperus esculentus tubers, showing CeSAD, especially CeSAD1, as the target gene in genetic modification to increase oil and oleic yields in oil crops as well as stress tolerance. Highlights: Two cDNAs encoding stearoyl-ACP desaturase are cloned from Cyperus esculentu tube . CeSAD1 expression is highly correlated with oil & oleic acid accumulation in tubers. CeSADs have SAD enzyme activity, with CeSAD1 having oleic acid-specific preference. CeSAD expression greatly increases oil biosynthesis in yeast cells & tobacco plants. CeSAD1 overexpression significantly promotes host tolerance against cold stress.